Identification of differentially expressed miRNAs and mRNAs in synovial of osteoarthritis via RNA-sequencing - Yu Zhou; Zhicong Wang; Xi Chen; Jianjun Zhang; Ling Yang; Shuping Liu; Yuehong Liu (BMC, 2020)
Abstract Background Osteoarthritis (OA) is the most common form of arthritis and a leading cause of disability. This study attempted to investigate the key mRNAs and miRNAs related to OA. Patients and methods From April 17th, 2018 to May 17th, 2018, five patients with OA and three normal controls were enrolled in this present study. To identify the differentially expressed mRNAs (DEmRNAs) and miRNAs (DEmiRNAs) between patients with OA and normal controls, RNA-sequencing was performed. Then, DEmiRNA-target DEmRNAs analysis and functional annotation of DEmiRNA-target DEmRNAs were performed. To validate the RNA-sequencing results, quantitative real time-PCR (RT-PCR) and western blot analysis were performed as well. Results A total of 1068 DEmRNAs, 21 DEmiRNAs and 395 DEmiRNA-DEmRNA pairs were identified in synovial tissues of patients with OA. The functional annotation of DEmiRNA-target DEmRNAs revealed that Pathways in cancer and PI3K-Akt signaling pathway were significantly enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. QRT-PCR and western blot results revealed that except for TLR7, the expression level of the others was consistent with the RNA-sequencing results, generally. Conclusion The findings of this present study may provide new clues for the roles of DEmRNAs and DEmiRNAs in the pathogenesis of OA.